Radiative non-coaxial rotating flow for viscous fluid over accelerated disk with MHD and porosity effects - Wan Nura’in Nabilah Noranuar,; Ahmad Qushairi Mohamad,; Lim, Yeou Jiann; Sharidan Shafie,; Ling, Dennis Chuang Ching (Penerbit Universiti Kebangsaan Malaysia, 2022)
An analytical solution to analyze the effects of radiation, magnetic, and permeability in an accelerating non-coaxial rotation phenomenon is not yet reported in the previous studies. Therefore, a radiative mixed convection flow for non-coaxial rotating MHD viscous fluid in a porous medium past an accelerated disk is studied. The fluid motion in this problem is induced by two sources which are rotating and buoyancy force. The dimensional coupled differential equations subjected to initial and accelerated boundary conditions are transformed to the dimensionless equations by utilizing appropriate dimensionless variables. The Laplace transform technique is applied to generate the closed form analytical solution for this problem. The impacts of Prandtl number, Grashof number, radiation, magnetic, porosity, and accelerated parameters on the temperature and velocity fields are illustrated graphically. The velocity and temperature profiles satisfy both the initial and boundary conditions, and the present results are found in accordance to the published work. The velocity is improved with the assistance of acceleration, radiation and porosity, while the implementation of magnetic field causes the opposite effect. Increasing radiation leads to the growth of the thermal boundary layer as well as reducing the heat transmission rate. This result can significantly contribute to the designing of heating systems because the imposition of radiation able to sustain an environment for a specific temperature. The obtained analytical solution can be used to check the correctness of the solution obtained from the numerical and experimental studies.